2018
DOI: 10.1073/pnas.1809285115
|View full text |Cite
|
Sign up to set email alerts
|

Copper inhibits peptidoglycan LD-transpeptidases suppressing β-lactam resistance due to bypass of penicillin-binding proteins

Abstract: The peptidoglycan (PG) layer stabilizes the bacterial cell envelope to maintain the integrity and shape of the cell. Penicillin-binding proteins (PBPs) synthesize essential 4–3 cross-links in PG and are inhibited by β-lactam antibiotics. Some clinical isolates and laboratory strains of Enterococcus faecium and Escherichia coli achieve high-level β-lactam resistance by utilizing β-lactam–insensitive LD-transpeptidases (LDTs) to produce exclusively 3–3 cross-links in PG, bypassing the PBPs. In E. coli, other LDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 45 publications
3
76
0
Order By: Relevance
“…Addition of NaCl to the buffer decreased probe degradation, but had a negative impact on reaction rate and was therefore omitted from subsequent assays (Figure S4). As metal ions (i.e., Cu 2+ ) are thought to interact directly with Cys354 of Ldt Mt2 , sodium ions in the buffer might similarly slow reaction with probes 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Addition of NaCl to the buffer decreased probe degradation, but had a negative impact on reaction rate and was therefore omitted from subsequent assays (Figure S4). As metal ions (i.e., Cu 2+ ) are thought to interact directly with Cys354 of Ldt Mt2 , sodium ions in the buffer might similarly slow reaction with probes 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the underlying molecular mechanisms remain unclear, media osmolarity affects the growth of cells harboring conditional mutants of division genes, dictates essentiality of FtsEX for division, and modulates cell size in E. coli [44,73,74]. Extracellular metal availability also alters the activity of several nonessential cell wall enzymes [7577]. Further exploration promises to illuminate additional environmental determinants modulating the activity of not only enzymes involved in bacterial cell wall synthesis, but also other extracytoplasmic processes.…”
Section: Discussionmentioning
confidence: 99%
“…10 Antimicrobial copper coatings on orthopaedic material like titanium and titanium alloy have also been reported by Wan et al 11 The alternative cycle of cupric and cuprous ions trigger an intracellular redox potential which can lead to instability and therefore cell damage. 12 In addition, 'Fenton type' chemistry in the presence of molecular oxygen following the production of superoxide and other reactive oxygen species can cause detrimental cellular damage to the bacteria. 12,13 Bacterial cell wall synthesis is carried out by enzymes known as DD-transpeptidases which are the target of b-lactams antibiotics such as penicillin.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, 'Fenton type' chemistry in the presence of molecular oxygen following the production of superoxide and other reactive oxygen species can cause detrimental cellular damage to the bacteria. 12,13 Bacterial cell wall synthesis is carried out by enzymes known as DD-transpeptidases which are the target of b-lactams antibiotics such as penicillin. Some bacteria produce an alternative enzyme known as LD-transpeptidase which allows cell wall synthesis even in the presence of b-lactams and a recent study showed that copper ions can inhibit LD-transpeptidases thus rendering b-lactamresistant bacteria susceptible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation